Gut microbiota-derived succinate aggravates acute lung injury after intestinal ischaemia/reperfusion in mice. Issue 2 (16th February 2023) - Wang, Yi-Heng; Yan, Zheng-Zheng; Luo, Si-Dan; Hu, Jing-Juan; Wu, Mei; Zhao, Jin; Liu, Wei-Feng; Li, Cai; Liu, Ke-Xuan
Introduction: Acute lung injury (ALI) is a major cause of morbidity and mortality after intestinal ischaemia/reperfusion (I/R). The gut microbiota and its metabolic byproducts act as important modulators of the gut–lung axis. This study aimed to define the role of succinate, a key microbiota metabolite, in intestinal I/R-induced ALI progression. Methods: Gut and lung microbiota of mice subjected to intestinal I/R were analysed using 16S rRNA gene sequencing. Succinate level alterations were measured in germ-free mice or conventional mice treated with antibiotics. Succinate-induced alveolar macrophage polarisation and its effects on alveolar epithelial apoptosis were evaluated in succinate receptor 1 ( Sucnr1 )-deficient mice and in murine alveolar macrophages transfected with Sucnr1 -short interfering RNA. Succinate levels were measured in patients undergoing cardiopulmonary bypass, including intestinal I/R. Results: Succinate accumulated in lungs after intestinal I/R, and this was associated with an imbalance of succinate-producing and succinate-consuming bacteria in the gut, but not the lungs. Succinate accumulation was absent in germ-free mice and was reversed by gut microbiota depletion with antibiotics, indicating that the gut microbiota is a source of lung succinate. Moreover, succinate promoted alveolar macrophage polarisation, alveolar epithelial apoptosis and lung injury during intestinal I/R. Conversely, knockdown of Sucnr1 or blockage of SUCNR1 in vitro and in vivo reversed the effects of succinate by modulating the phosphoinositide 3-kinase-AKT/hypoxia-inducible factor-1α pathway. Plasma succinate levels significantly correlated with intestinal I/R-related lung injury after cardiopulmonary bypass. Conclusion: Gut microbiota-derived succinate exacerbates intestinal I/R-induced ALI through SUCNR1-dependent alveolar macrophage polarisation, identifying succinate as a novel target for gut-derived ALI in critically ill patients. Succinate accumulation in the lungs is associated with the imbalance of succinate-producing and -consuming bacteria in the gut during intestinal ischaemia/reperfusion. Lung injury was exacerbated by succinate via alveolar macrophage polarisation. https://bit.ly/3fTR9AM